Georgia : Seventh Review Under the Extended Fund Facility Arrangement and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Georgia. (IMF Staff Country Reports; Country Report, 2020)
Georgia's performance under the Extended Arrangement has been positive, but the country is now facing a pronounced economic slowdown. Domestic and external demand remain weak, and service sector activity remains sluggish. Staff projects the economy to shrink by 5.1 percent this year followed by a gradual recovery.